Dengue outbreaks in a city with recent transmission in São Paulo state, Brazil - Prestes-Carneiro, Luiz Euribel; Barbosa Souza, Alana; Belussi, Gabriella Lima; Grande, Guilherme Henrique Dalaqua; Bertacco, Elaine Aparecida Maldonado; Vieira, André Gonçalves; Flores, Edilson Ferreira [UNESP] (Taylor & Francis, 2023)
We investigated the distribution of dengue cases, solid waste deposits (SWDs), forest fragments, water drainage, population income, and the possible association with dengue outbreaks in Presidente Prudente, São Paulo, Brazil. An urban setting with recent transmission. Data were obtained from public agencies. Kernel density maps of the variables were constructed. From 2015 to 2021, 33026 cases of dengue were reported; the incidence and mortality rate were highest in 2016. The number of cases decreased during the COVID-19 pandemic (2020 and 2021) compared with 2019, but alarming rates were registered in 2022. In 2015, 56 points of SWDs were identified, with an increase of 1.6-fold in 2020 and 2021. Multivariate analysis showed a positive correlation between the density of dengue cases and SWDs with the highest correlation (0.70) in 2020. Identifying these areas could guide public health authorities in surveillance measures and improvements in health care infrastructure.
Keywords: Dengue; environment; forest fragments; solid waste deposits; water drainage